2002
DOI: 10.1002/1521-3773(20020118)41:2<329::aid-anie329>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electrical Conductivity and Self-Assembly of Regioregular Polythiophene by Block Copolymerization: Nanowire Morphologies in New Di- and Triblock Copolymers We gratefully acknowledge support from the NSF (CHE-9807707).

Abstract: Over two decades ago the discovery of electrical conductivity in conjugated polymers spurred a tremendous amount of effort aimed at the development of practical conducting plastics. [1] One of the primary motivations was the hope of fabricating inexpensive, lightweight conducting materials. Those efforts have been coming to fruition in recent years with the development of polymer-based light-emitting diodes, [2] field-effect transistors, [3] elements for active matrix displays, [4] and all-polymer integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
340
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 413 publications
(353 citation statements)
references
References 30 publications
12
340
1
Order By: Relevance
“…The polymers and electrodes used were fabricated as described previously. 19 All polymers reported in this study are synthesized by the modified McCullough route using 2-methylthiophene as an end-capping agent 28 and have regioregularities greater than 98% as measured by 1 H NMR. MW was adjusted by controlling the ratio of 2-methylthiophene to the monomer.…”
Section: Methodsmentioning
confidence: 99%
“…The polymers and electrodes used were fabricated as described previously. 19 All polymers reported in this study are synthesized by the modified McCullough route using 2-methylthiophene as an end-capping agent 28 and have regioregularities greater than 98% as measured by 1 H NMR. MW was adjusted by controlling the ratio of 2-methylthiophene to the monomer.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18][19] Block copolymers composed of an electron-donating and an electronaccepting block are therefore particularly interesting for PV applications and are presently studied worldwide by several research groups. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Particularly, rod-coil block copolymers using poly[(2,5-di(2-ethyl)hexyloxy)-1,4-phenylenevinylene] (DEH-PPV) as electron donor and various coil blocks (such as polystyrene or polybutylacrylate) with covalently linked fullerene moieties as electron acceptor have been investigated intensively. [23][24][25][26][27][28] Although these studies have given considerable insight into the physics of copolymer self-assembly, their efficient utilization as the active layer in PV devices has not yet been fully demonstrated.…”
mentioning
confidence: 99%
“…[4][5][6][7] Very recently, we have developed an endgroup functionalization methodology of HT-PATs that allows for the synthesis of a plethora of well-defined block copolymers that form nanowires with high electrical conductivity. 7 Here, we have discovered that the nickel-initiated regioregular polymerization of alkylthiophenes proceeds by a chain growth mechanism and does not occur by the accepted step growth mechanism. 8 We also observed that the degree of polymerization of the synthesized poly(alkylthiophenes) increases with the conversion and can be predicted by the molar ratio of monomer to nickel initiator.…”
mentioning
confidence: 99%
“…2,3 Regioregular polythiophenes have led to a multitude of important and novel nano-and microscale electronic materials and devices. [4][5][6][7] Very recently, we have developed an endgroup functionalization methodology of HT-PATs that allows for the synthesis of a plethora of well-defined block copolymers that form nanowires with high electrical conductivity. 7 Here, we have discovered that the nickel-initiated regioregular polymerization of alkylthiophenes proceeds by a chain growth mechanism and does not occur by the accepted step growth mechanism.…”
mentioning
confidence: 99%